THE ROLE OF MATERIALS IN THE LANGUAGE CLASSROOM: FINDING THE BALANCE FOR B2 LEVEL (Academia Science Repository, 2023)
This article highlights the delicate balance the materials developer needs to achieve between expanding classroom horizons and dominating the interaction which underlies the learning process.